Convergence of Customary Law and Sharia in the Kazakh Steppe Based on Russian Reports (First Half of the 19th Century) - MAZHITOVA, Zhanna; ATANAKOVA, Karlygash; USKEMBAYEV, Kanat (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT In the XVIII century, the Russian Empire entered Kazakh lands. It contributed to the spread of Islam among the Kazakhs. By the beginning of the 19th century, legal pluralism appeared on the territory of the Steppe. Customary law and Sharia mixed up in the process of parallel development, complemented each other, and eventually found the most acceptable option for coexistence. The choice between different judicial practices, i.e., Sharia or customary law, on the territory of the Steppe led to the fact that the Russian government eventually supported the adat in order to reduce the influence of Islam on the local population.RESUMEN En el siglo XVIII, el Imperio ruso entró en tierras kazajas. Contribuyó a la difusión del Islam entre los kazajos. A principios del siglo XIX, el pluralismo legal apareció en el territorio de la Estepa. El derecho consuetudinario y la sharia se mezclaron en el proceso de desarrollo paralelo, se complementaron y finalmente encontraron la opción más aceptable para la convivencia. La elección entre diferentes prácticas judiciales, es decir, la sharia o el derecho consuetudinario, en el territorio de la Estepa llevó al hecho de que el gobierno ruso finalmente apoyó el adat para reducir la influencia del Islam en la población local.